Ressonância magnética da coluna vertebral de crianças e adolescentes com neurofibromatose tipo 1 - Nogueira, Fabiano Morais (2013)
Introduction: Neurofibromatosis type 1 (NF1) is among the most common genetic disorders caused by mutations on chromosome 17 and characterized by a broad spectrum of clinical manifestations. Scoliosis is one of the most frequently musculoskeletal alterations and may be accompanied by dystrophic changes and tumor-related spine. Objective: To identify the prevalence of tumors and dystrophic changes in the spine of children and adolescents with neurofibromatosis type 1 assessed by magnetic resonance imaging and to analyze possible correlations between these findings and the presence of spinal deformities. Methods: Twenty-two patients with NF1, less than 21 years, underwent clinical and magnetic resonance imaging of the spine between September 2009 and July 2011. The group had 13 girls and 9 boys, with a mean age of 13.04 years (range 4-20 years). Only patients with clinical evidence of scoliosis were subjected to x-ray total spine for measuring the Cobb angle. Statistical analysis was performed using the Statistical Analysis Systems. The level of significance for all tests was 5%. Results: Scoliosis was diagnosed in 13 patients at the apex of the curve in the thoracic region predominantly represented by nine patients (69.23%). Excluding 3 patients did not undergo X-ray, 4 patients presented with dystrophic scoliosis mean Cobb angle of 57.75 degrees and 6 patients with non-dystrophic scoliosis and average Cobb angle of 15.33 degrees (p=0.0017). Neurofibromas associated to the spine were present in 9 patients (40.91%) and predominated in children older than 12 years (77.7%) but without statistical significance (p=0.2031). Among the patients with neurofibromas, 6 patients (66.7%) had associated with scoliosis (p=0.674). The dystrophic changes were found in 5 patients (22.72%), all with scoliosis. The vertebral erosion was the most frequent finding dystrophic, with 31 lesions in 25 vertebrae, mostly located in the posterior region of the vertebra and thoracic spine (54.84%). The vertebral erosions were associated with scoliotic curve in 96.7% of cases, dural ectasia in 87.5% of cases and patients with the greatest number of these lesions had a higher magnitude of their curves (Pearson=0.8275; p=0.0838). One patient had multiple meningoceles and one patient had two ribs intracanal, both associated with dystrophic curves. Conclusion: The evaluation with magnetic resonance imaging of the spine was able to identify the main tumor and dystrophic changes, correlate with the presence of vertebral deformities and analyze their distribution area of the curve. The vertebral erosion was the most common finding in dystrophic scoliosis curve and showed a tendency of correlation between the curves more severe and patients with higher number of vertebrae eroded. Neurofibromas that were associated with the spine were mainly found in the older children and tended to occur more frequently in the patients with scoliosis. In both cases, studies with larger samples are needed to assess whether these trends are evident.